Impact Time Guidance Law Considering Autopilot Dynamics Based on Variable Coefficients Strategy for Maneuvering Target. (15th June 2015) - Shang, Wei; Guo, Jie; Tang, Shengjing; Ma, Yueyue; Zhang, Yao
Abstract : This paper investigates the terminal guidance problem for the missile intercepting a maneuvering target with impact time constraint. An impact time guidance law based on finite time convergence control theory is developed regarding the target motion as an unknown disturbance. To further improve the performance of the guidance law, an autopilot dynamics which is considered as a first-order lag is taken into consideration. In the proposed method, the coefficients change with the relative distance between missile and target. This variable coefficient strategy ensures that the missile impacts the target at the desired time with little final miss distance. Then it is proved that states of the guidance system converge to sliding mode in finite time under the proposed guidance law. Numerical simulations are presented to demonstrate the effectiveness of the impact time guidance law with autopilot dynamics (ITGAD).